The metamorphic and anatectic history of Archaean metapelitic granulites from the South Marginal Zone, Limpopo Belt, South Africa. - Nicoli, Gautier (Stellenbosch : Stellenbosch University, 2015)
Thesis (DSc)--Stellenbosch University, 2015.